90 Socio-Demographic and Medical Factors in A Multi-Ethnic Cohort of COVID Deaths. (16th March 2021) - Patel, M; Umasankar, U; McCall, B
Abstract: Introduction: Whilst most patients during the COVID pandemic made an uneventful recovery, there was a significant minority in whom the disease was severe and unfortunately fatal. This survey aims to examine and evaluate risk factors for those patients who died of COVID and to identify any markers for improvement in the management of such patients during future COVID surges. Methods: Medical records of all patients who died within a multi-ethnic, inner city acute district general hospital over a 6-week period in 2020 were examined. Data collected included demographic details, medical comorbidities, and type of ward where they received care. Multivariable analysis using stepwise backward logistic regression was conducted to examine independent risk factors for these patients. Results: Of 275 deaths, 204 were related to COVID. Compared to non-COVID deaths(n = 71), there were no age differences. There were significantly more deaths in males (58%vs39%, P < 0.001)) and in Black African and South Asian groups. 18% of COVID deaths were those who were not frail (Frailty Rockwood Scale 1–3) whereas there were no non-COVID deaths in this group(P < 0.001). 69% of COVID deaths occurred in general medical wards whereas 19% in critical care units (90% and 7% for non-COVID deaths, p < 0.001). COVID patients died more quickly compared to non-COVID patients (length of stay mean, 11vs21, p < 0.001). Medical factors prevalent in >20% of COVID deaths included Diabetes, Hypertension, Chronic Heart Disease, Chronic Kidney Disease, and Dementia. Multivariable analyses showed males (OR 1.9), age > 70(OR 2.0), frailty (OR 2.3) were independent risk factors for COVID deaths. Discussion: Compared to non-COVID deaths, COVID deaths were more common in previously well individuals, males, Black African and South Asian ethnicity, but multivariable analyses showed males, age > 70 and frailty were independent risk factors for COVID deaths. This survey indicates that greater psychological support may be required for healthcare workers on general medical wards who looked after greater proportion of COVID deaths.